NUTRITIONAL THERAPY IN MALNOURISHED YOUNG ADOLESCENT: FROM EPILEPTIC STATE TO CATCH UP GROWTH - Faradilah, Andi; January, Rima; As'ad, Suryani; Jalaluddin, Syatirah (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
Epilepsy and malnutrition in children are a vicious circle. Epilepsy with non-treated recurrent seizures could lead to malnutrition. Conversely, malnutrition which results in macronutrient and micronutrient deficiencies also potential to trigger seizures. We reported an adolescent, male, 14 years 6 months, with epileptic state accompanied by malnutrition status. In this case, a repeated seizures cause the unconscious level of patient and at risk of respiratory failure. Multidisciplinary therapy was arranged by anesthesiologist, pediatrician, and clinical nutritionist. The treatments began with procedure of a ventilator installation, anticonvulsant drugs, and administration of a nasogastric tube for accessing nutrition intake. Nutrition therapy focused on managing diet in  critical ill children and attention to undernourished conditions that require long-term treatment. The target of nutrition calorie was achieved on day 6-8 of treatment through enteral to oral diet.  Finally, nutrition education for catch-up growth was given to the families to be applied during the recovery and rehabilitation period at home.